Goods and Services of Marine Bivalves - Smaal, Aad C; Ferreira, Joao G; Grant, Jon; Petersen, Jens K; Strand, Øivind (Springer Nature, 2019)
The aim of this open access book is to review and analyse the goods and services of bivalve shellfish. How they are defined, what determines the ecological functions that are the basis for the goods and services, what controversies in the use of goods and services exist, and what is needed for sustainable exploitation of bivalves from the perspective of the various stakeholders. The book is focused on the goods and services, and not on impacts of shellfish aquaculture on the benthic environment, or on threats like biotoxins; neither is it a shellfish culture handbook although it can be used in evaluating shellfish culture. The reviews and analysis are based on case studies that exemplify the concept, and show the strengths and weaknesses of the current applications. The multi-authored reviews cover ecological, economic and social aspects of bivalve goods and services. The book provides new insights for scientists, students, shellfish producers, policy advisors, nature conservationists and decision makers. This book is open access under the CC BY license.